THE TEST RESULTS AND CALCULATION OF THE EROR VALUE OF THE RATIO AND SATURATION POINT AT CURRENT TRANSFORMER FEEDER KUALA DUA SUBTATION - Ilhamdi, Muhammad; Gani, Usman A.; Rajagukguk, Managam (Faculty of Engineering, Universitas Tanjungpura, 2023)
Electrical energy at this time is a very important need to meet the needs of humans, such as lighting, factory machinery, household electricity, and other needs. Electricity flowing from the plant is channeled through transmission lines to be distributed to low- and medium voltage customers. In the process of distributing electrical energy, a device is needed to lower the voltage, namely a transformer. For the purposes of measurement and protection in electrical installations, a current transformer is needed to convert the amount of current on the primary side of large-scale electrical installations into small-scale current quantities more precisely and accurately. Determine the accuracy class of the current transformer to be able to transform primary into secondary. The excitation current will cause deviations from the measurement results. This deviation is commonly known as a transformation error or ratio error. Every single current transformer that PLN will use must meet the criteria of the IEC 60044-1 standard. From the data manager of current transformers in 30 phases at the Kuala Dua substation, it can be concluded that the current transformers with a ratio of 300/5A, 400/5A, 500/5A and 600/5A, core metering accuracy classes of 0.2 S, 0.5, and 1, 5P and 10P protection core accuracy classes. With the maximum error of the metering core ratio of ±0.2%, ±0.5%, and ±1%, and the maximum error of the protection core ratio of ±3% and ±5%.